Early career family physician perspectives on their residency experience and practice choices in Canada: a qualitative study - Moravac, Catherine; Grudniewicz, Agnes; Scott, Ian; Randall, Ellen; Goldsmith, Laurie; Marshall, Emily G; Jones, Lori; Lavergne, M Ruth (Canadian Medical Education Journal, 2024)
Background: Though there are more family physicians in Canada than ever before, and residency programs are expanding, gaps in access to comprehensive care remain. This study aimed to describe and understand the role residency training experiences played in shaping practice choices, including the provision of comprehensive community-based care, among early career family physicians. Methods: A secondary analysis of sixty-three (63) qualitative interviews was conducted on data from a larger mixed method study on practice patterns and choices of early career Canadian family physicians. We utilized Braun and Clarke’s six phases of reflexive thematic analysis on portions of transcripts concerning residency training experiences. Results: Participants described positive residency training experiences that shaped practice choice with respect to preceptors and mentorship, experiences of longitudinal care, breadth of exposure, and preparedness for comprehensive clinical practice. Woven through these four domains were “points of tension” and “hidden truths”. Points of tension included: i) the promotion of an idealized professional identity and practice that was difficult to uphold, ii) lack of representation among faculty/preceptors with respect to age and gender, at some sites, and iii) frustration about the lack of opportunities for interprofessional collaborative practices that reflected training experiences. Hidden truths included: i) lack of preparation to run a business, ii) high administrative workload, iii) realities of payment models, and iv) the range of roles available for family physicians beyond the provision of comprehensive care. Conclusions: Findings highlight opportunities for educational reform supporting the transition from residency to practice alongside the importance of addressing systemic factors beyond training which impact physicians’ choices regarding comprehensive care.